PWE-117 The role of repeat liver biopsies in autoimmune hepatitis: clinical practice and outcomes. (22nd June 2015) - Mathew, S; Narang, R; Pericleous, M; Ramu, A; Berry, P; Cheent, K; Lewis, H; Kousparos, G; Ala, A
Abstract : Introduction: The role of repeat liver biopsies in established Autoimmune hepatitis (AIH) is unclear, with limited data on clinical practice and outcomes, and with variation in biopsy practice between physicians. Method: We undertook a retrospective review of all patients with AIH who underwent a repeat liver biopsy between 2002–2013 at Frimley Park Hospital (Surrey, England); serving a population 430, 000. The indication for repeat biopsy, liver histology and serological markers were recorded, as well as the clinical outcome/management resulting from each procedure. Results: 17 patients were identified, all who were on treatment for AIH at the time of repeat biopsy. Clinical indications for repeat biopsy included: disease assessment/staging (34%) clinical deterioration (24%), diagnostic uncertainty (24%), medication withdrawal/remission (12%) and insufficient (Bx) sample (6%). Median time between 1 st and repeat biopsy was 24 months (range 1–108 months). Overall 10/17 (59%) patients had normal LFTs and 12/17 (71%) had normal IgG levels at the time of repeat biopsy. Repeat biopsy led to a change in treatment (dose/regime) in 11/17(65%) patients. Baseline cirrhosis was seen in 3/17 (biopsy/imaging), and developed in a further 2 patients (12%) over 24–48months; both with raised IgG levels at the time of repeat biopsy. 9 patients had a repeat biopsy at ≤ 24months. Within this group 4/9(44%) patients had normal LFTs, and 6/9 (67%) had normal IgG levels. Repeat biopsy led to a change in treatment in 2/4 (50%) patients with normal LFTs and 4/6 (67%) with normal IgG levels. Fibrosis progression was seen in 1/4 (25%) with normal LFTs, and 2/6 (33%) with normal IgG levels. Interface hepatitis/periportal inflammation was present in all repeat biopsies. Conclusion: BSG and AASLD guidance suggest the use of repeat biopsies at 12–24 months following normalised transaminases to guide treatment withdrawal/maintenance, with IgG levels also thought predictive of histological response. However, the majority of repeat biopsies in our study were requested due to concerns of disease progression, rather than to assess for treatment withdrawal. Despite normalised LFTs/IgG levels, repeat biopsy led to treatment modification in more than half of this group; as well as demonstrating fibrosis progression and on-going histological activity. Our results support the need to individualise repeat liver biopsies to the needs of each patient. Disclosure of interest: None Declared.